Management of surgical affections in captive wild animals at Giza Zoo - Amany Abdelraouf Hassan Aly; Ibrahim Mohamed Ibrahim; Mervat Mahamoud Kamel; Wahid Salamah Elghoul (Cairo : Amany Abdelraouf Hassan Aly, 2009)
The sresent study was applied at Giza Zoological Garden (Egypt)during the period from March 2004 to March 2007 on a total number of 115 surgically affected cases of captive wild animals belong to five Orders including Primates,Carnivora,Proboscida,Perissodactyla,and Artiodactyla
Thesis (M.Sc.) - Cairo University - Faculty of Veterinary Medicine - Department of Surgery-Anesthesiology-Radiology
Issued also as CD
Keywords: Captive wild; Chemical restraint; Postcare